Is Getting Tough With Low-Risk Kids a Good Idea? The Effect of Failure to Appear Detention Stays on Juvenile Recidivism - Ogle, Meghan R. (Criminal justice policy review, 2019)
Although the juvenile justice system has adopted many alternatives to detention, the practice of detaining youth for failing to appear in court remains common. Despite its widespread use, it is unclear whether this form of detainment is harmful to juvenile offenders—especially to those who pose no credible threat to public safety. Accordingly, using data from the Florida Department of Juvenile Justice (FDJJ) and propensity score matching, we assess whether failure to appear (FTA) detention increases recidivism for low-risk youth. The results indicate that FTA detention increases official recidivism, technical recidivism, and re-detainment, and suggest that alternate policies be considered for low-risk juvenile offenders.